(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
A cross-sectional study was conducted in Iraq on 80 Iraqi children. This study aimed to assess the outcomes of developmental patterns and abnormalities in paediatric EMG studies. Samples were collected from several Iraqi hospitals over a one-year study period. Based on the results identified in this study, several conclusions were reached, including that electromyography (EMG) was classified as essential for determining the safety and health of the neuromuscular system in Iraqi children, and in our study, we found that the main type of EEG abnormality was neuropathy in 32 patients’ children. This may be due to several reasons, including the fact that these critically ill children may have used sedatives and tranquilizers, making it impossible to monitor changes in the nervous system. Studies have found that multiorgan dysfunction is associated with the severity of neuropathy; the lower the initial NCIS score, the greater the organ dysfunction. In short, EMG can be continuously monitored at the patient’s bedside, and its graphical presentation is intuitive, making it easily accessible even to non-specialists after training. Therefore, routine EMG monitoring should be performed on hospitalized neonates, especially those with critical illness, given their high rate of EEG abnormalities and their often-lacking neurological symptoms or signs.